(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
ational Security Strategies (NSS) and the institutions associated with them - in the case of Spain, the System, the Council and the Department of National Security - are recent realities in our country. Although they are still in the development stage they nevertheless represent a historic step forward. The adjective historic cannot be overemphasised. It is fundamental to the understanding of a process involving the two approved NSSs so far. The first of these was titled Estrategia Española de Seguridad. Una responsabilidad de todos - Spanish Security Strategy. A Responsibility for all- (June 2011, under the Socialist government) and the second: Estrategia de Seguridad Nacional. Un Proyecto compartido - National Security Strategy. A shared project - (May 2013, under the Popular Party government). Spain, one of the main players - if not the leading actor - in Western society in the sixteenth century, suffered a gradual decline in the seventeenth, recovered to a certain extent in the eighteenth, and went into free fall throughout the nineteenth and part of the twentieth century. The consolidation of democracy has been accompanied by an increase in Spain’s external role consistent with its relative share of power on the international stage - we are a medium power - and conditioned by a historical heritage that still weighs on our political elite and our society. However, viewed from an overall perspective, the trajectory of the last decades is extremely positive. It is also important that programme and institutional development should attract academic interest. It is further proof of the consolidation of security and defence studies in Spanish Universities. And it allows for the creation of synergies between the fields of national defence, security and external affairs, and the field of university research and teaching. En busca de una Estrategia de Seguridad Nacional offers an example of that win-win relationship. Its author, General Miguel Ángel Ballesteros, director of the Spanish Institute of Strategic Studies, has a long professional background in the Armed Forces and Defence and also as an academic, which allows him to combine the knowledge acquired by his practical experience with the rigour of scientific methodology. The book based on his doctoral thesis, which received the Extraordinary Doctorate Award, makes a very relevant contribution to the area of security studies and is of interest to those in political and technical spheres who design and implement national security strategies.